An inquiry into goal-setting practices with physical activity trackers - Konstanti, Chrysanthi; Karapanos, Evangelos (My University, 2018)
Goal setting is a theoretically grounded, empirically supported, and one of the most popular behavior change strategies employed by activity trackers – individuals set daily activity goals (e.g., 10000 steps) and continuous feedback on their performance is provided by the tracker. But while empirical studies are in abundance, we still have a limited understanding of users’ real-life practices with goal setting, which may well vary from what is theoretically assumed, and can have detrimental effects on behavior change. We present an ongoing study, consisting of an online survey, seeking to inquire into what goals people set, how they engage with feedback and the impact this has on their physical activity.
Keywords: Behavior change technologies; Goal setting; Physical activity trackers; Self-monitoring